THE EFFECTIVENESS OF EMPLOYEES PERFORMANCE LEADERSHIP STYLE, WORK MOTIVATION AND DISCIPLINE ON CV. VIO CATERING - Lasut, Stevie A. (Journal of Asean Studies on Maritime Issues, 2016)
Performance of employees of CV. Vio Catering can also be measured through completion duties effectively and efsien and perform its role and function and that all related linearly and positively related to the success of a company. Focus of this study is to analyze the influence of leadership style, work motivation and disciplines on employee performance in CV. Vio Catering, simultaneously and partially. Population of this research is all 54 employees of CV. Vio Catering. Sampling method used is saturated sampling method. Using a multiple regression as a analysis tool, this research found that there is a significant influence of leadership style, work motivation and disciplines on employee performance in CV. Vio Catering, simultaneously and partially. So based on this findings, is recommended that CV. Vio Catering needs to improve the employee performance by focusing an increasing in leadership style, work motivation and disciplines as factors to determine the increasing in employee performance.